Longitudinal Modelling of Body Mass Index from Birth to 14 Years - Chivers, P.; Hands, B.; Parker, H.; Beilin, L.; Kendall, Garth; Bulsara, Max (Karger, 2009)
Background: To examine the tracking of BMI from birth to age 14 years. Participants and Methods: Linear mixed model (LMM) analysis was used to model the trajectories of BMI (n = 1,403). Adiposity rebound was investigated for a subset of individuals (n = 173). Results: Adolescents who were overweight or obese at 14 years followed a different BMI trajectory from birth compared to those of normal weight. There was a difference between weight status groups for the timing of adiposity rebound (p <0.001) and BMI at nadir (p <0.001). The LMM depicted a significant difference in rate of change of BMI over time for males and females (p <0.001), with female BMI increasing at a faster rate, andfor weight status groups (p <0.005), with the obese cohort having the faster increase in BMI over time. BMI at birth was significantly lower for the normal weight cohort compared to the overweight (p = 0.029) and obese (p = 0.019) cohorts. Conclusion: This study introduces apowerful analytic tool, LMM, to model BMI and shows that weight status at 14 years is the result of a distinct path in earlier years. Compared to their normal weight peers, overweight and obese adolescents experience an earlier adiposity rebound, with a higher BMI at rebound.